2007
DOI: 10.1007/s00415-007-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological consequences of endarterectomy and endovascular angioplasty with stent placement for treatment of symptomatic carotid stenosis

Abstract: These results provide some reassurance that CAS is not associated with greater cognitive deterioration than CEA is.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…5, Twenty-five reported on cognitive outcome after CEA, 5,17-26,28 -42 4 after CAS, [43][44][45][46] and 3 after CEA versus CAS. 18,27,47 Overall, 16 used one or more control groups varying from healthy subjects to patients affected by different diseases. 18 Ten focused exclusively on symptomatic 5,17,21,28,33,35,43,45,27,47 and one on asymptomatic patients.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…5, Twenty-five reported on cognitive outcome after CEA, 5,17-26,28 -42 4 after CAS, [43][44][45][46] and 3 after CEA versus CAS. 18,27,47 Overall, 16 used one or more control groups varying from healthy subjects to patients affected by different diseases. 18 Ten focused exclusively on symptomatic 5,17,21,28,33,35,43,45,27,47 and one on asymptomatic patients.…”
Section: Search Resultsmentioning
confidence: 99%
“…18,27,47 Overall, 16 used one or more control groups varying from healthy subjects to patients affected by different diseases. 18 Ten focused exclusively on symptomatic 5,17,21,28,33,35,43,45,27,47 and one on asymptomatic patients. 19 Time of cognitive assessment varied from 24 hours to 8 years after revascularization and 4 reported at 1 year or later (3 and 8 years).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 12 RCTs3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 that have compared carotid endarterectomy (CEA) with carotid artery stenting (CAS) in patients with significant carotid stenosis, only five3, 9, 10, 12, 14 provided information on the time from the index event to revascularization. CREST (Carotid Revascularization Endarterectomy versus Stenting Trial)10 reported the shortest median interval; this was still 22 days for CEA and 18 days for CAS.…”
mentioning
confidence: 99%